A soft functional mitral valve model prepared by three-dimensional printing as an aid for an advanced mitral valve operation. (3rd February 2022) - Yang, Yuanting; Wang, Hao; Song, Hongning; Hu, Xiaoping; Hu, Rui; Cao, Sheng; Guo, Juan; Zhou, Qing
Abstract: OBJECTIVES: The goal of this study was to build a soft mitral valve (MV) model for surgical simulation to aid with an advanced MV operation. METHODS: Soft three-dimensional models of the MV were constructed by the mould-modelling method using silicone. The properties of the material used were tested and compared with those of the valve tissue. Then, the accuracy of the three-dimensional model was assessed from the perspectives of the pathological and morphological parameters. Thereafter, surgical simulation of MV repair, closure of the perforation and transcatheter MV replacement were simulated using our model. Two experienced surgeons were invited to perform and evaluate the fidelity and softness of the model. Morphological changes in the MV and the potential compression of the device on surrounding cardiac tissue were also measured after simulation. RESULTS: The soft MV model was successfully constructed by the mould-modelling method. The property of the material used was closer to that of valve tissue than to that of the rigid model. In addition, the pathological details and morphological measurements of the three-dimensional model were consistent with the surgical findings. The simulated surgical procedure was successful using our model. Morphological changes, including the ratio of the leaflet/annulus area and the coaptation depth, were closely correlated with the regurgitation left after MV repair, which might be an indicator of the surgical effects. The results of this study demonstrated the great advantages of our constructed soft model in exploring the interaction of the device with the surrounding tissue. These advantages were not obtained using the rigid model in a previous study. CONCLUSIONS: The soft MV model was successfully constructed using the mould-modelling method, and its physical properties were similar to those of heart tissue. In addition, the constructed model exhibited great advantages in surgical simulation and clinical application compared with the anatomical model. Abstract : In recent years, the aetiology of mitral valve (MV) disease has changed significantly and degenerative disease accounts for an increasing proportion of cases.